Solutions

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 153776 695 . . . 0.3183098 861837906 7153776 752674502 34 . . . 0.3183098 861837906 7153776 752674502 87 . . . f (h) − f (0) e−1/h = lim , let t = 1/h then h = 1/t and h→0 h→0 h h 2 28. (a) f (0) = lim 2 e−1/h t 1 e−1/h = lim te−t = lim t2 = lim = 0 so = 0, similarly lim t2 − t→+∞ t→+∞ e t→+∞ 2te h h h→0 2 lim h→0+ f (0) = 0. 2 397 Chapter 11 (b) The Maclaurin series is 0 + 0 · x + 0 · x2 + · · · = 0, but f (0) = 0 and f (x) > 0 if x = 0 so the series converges to f (x) only at the point x = 0. EXERCISE SET 11.10 1 = 1 − x + x2 − · · · + (−1)k xk + · · · ; R = 1. 1+x 1 (b) Replace x with x2 : = 1 + x2 + x4 + · · · + x2k + · · · ; R = 1. 1 − x2 1 (c) Replace x with 2x : = 1 + 2x + 4x2 + · · · + 2k xk + · · · ; R = 1/2. 1 − 2x 1. (a) Replace x with −x : (d) 1/2 1 1 1 1 1 1 = ; replace x with x/2 : = + 2 x + 3 x2 + · · · + k+1 xk + · · · ; R = 2. 2−x 1 − x/2 2−x 22 2 2 2. (a) Replace x with −x : ln(1 − x) = −x − x2 /2 − x3 /3 − · · · − xk /k − · · · ; R = 1. (b) Replace x with x2 : ln(1 + x2 ) = x2 − x4 /2 + x6 /3 − · · · + (−1)k−1 x2k /k + · · · ; R = 1. (c) Replace x with 2x : ln(1+2x) = 2x − (2x)2 /2+(2x)3 /3 −· · · +(−1)k−1 (2x)k /k + · · · ; R = 1/2. (d) ln(2 + x) = ln 2 + ln(1 + x/2); replace x with x/2 : ln(2 + x) = ln 2 + x/2 − (x/2)2 /2 + (x/2)3 /3 + · · · + (−1)k−1 (x/2)k /k + · · · ; R = 2. 1 1·3 2 1·3·5 3 1 =1− x+ 2 x− 3 x + · · ·, so 2 2 · 2! 2 · 3! 1+x 1 1 1 1·3 2 1·3·5 3 x − 13/2 x + ··· = 1/2 − 5/2 x + 9/2 =√ 2 2 2 · 2! 2 · 3! 2 1 + x/2 3. (a) From Section 11.9, Example 5(b), √ (2 + x)−1/2 (b) Example 5(a): 4. (a) 1 1 = 1 − 2x + 3x2 − 4x3 + · · ·, so = 1 + 2x2 + 3x4 + 4x6 + · · · (1 + x)2 (1 − x2 )2 1 1/a = = 1/a + x/a2 + x2 /a3 + · · · + xk /ak+1 + · · · ; R = |a|. a−x 1 − x/a (b) 1/(a + x)2 = = 1 1 1 = 2 1 − 2(x/a) + 3(x/a)2 − 4(x/a)3 + · · · a2 (1 + x/a)2 a 2 3 4 1 − 3 x + 4 x2 − 5 x3 + · · · a2 a a a 23 3 25 5 27 7 x + x − x + · · ·; R = +∞ 3! 5! 7! 1 1 (c) 1 + x2 + x4 + x6 + · · ·; R = +∞ 2! 3! 5. (a) 2x − 6. (a) 1 − (b) x2 4 (b) 1 − 2x + 2x2 − x3 + · · ·; R = +∞ 3 π2 4 π4 6 π6 8 x+ x− x + · · · ; R = +∞ (d) x2 − 2 4! 6! 22 2 24 4 26 6 x + x − x + · · ·; R = +∞ 2! 4! 6! 12 1 1 1 1 + x + x + x3 + · · · = x2 + x3 + x4 + x5 + · · ·; R = +∞ 2! 3! 2! 3! (c) x 1 − x + (d) x2 − 1 12 x − x3 + · · · 2! 3! = x − x2 + 16 1 1 x + x10 − x14 + · · ·; R = +∞ 3! 5! 7! 13 1 x − x4 + · · ·; R = +∞ 2! 3! Exercise Set 11.10 398 7. (a) x2 1 − 3x + 9x2 − 27x3 + · · · = x2 − 3x3 + 9x4 − 27x5 + · · ·; R = 1/3 (b) x 2x + 23 3 25 5 27 7 x + x + x + ··· 3! 5! 7! (c) Substitute 3 x − x3 + 2 8. (a) = 2x2 + 23 4 25 6 27 8 x + x + x + · · ·; R = +∞ 3! 5! 7! 3/2 for m and −x2 for x in Equation (22) of Section 11.9, then multiply by x: 35 1 x + x7 + · · ·; R = 1 8 16 −x x = = −x 1 + x + x2 + x3 + · · · = −x − x2 − x3 − x4 − · · · ; R = 1. x−1 1−x (b) 3 + 34 3 3 x + x8 + x12 + · · ·; R = +∞ 2! 4! 6! (c) From Table 11.9 with m = −3, (1 + x)−3 = 1 − 3x + 6x2 − 10x3 + · · ·, so x(1 + 2x)−3 = x − 6x2 + 24x3 − 80x4 + · · ·; R = 1/2 9. (a) sin2 x = 1 22 1 24 26 (1 − cos 2x) = 1 − 1 − x2 + x4 − x6 + · · · 2 2 2! 4! 6! = x2 − 23 4 25 6 27 8 x + x − x + ··· 4! 6! 8! (b) ln (1 + x3 )12 = 12 ln(1 + x3 ) = 12x3 − 6x6 + 4x9 − 3x12 + · · · 10. (a) cos2 x = 1 22 1 24 26 (1 + cos 2x) = 1 + 1 − x2 + x4 − x6 + · · · 2 2 2! 4! 6! = 1 − x2 + 23 4 25 6 x − x + ··· 4! 6! (b) In Equation (17) of Section 11.9 replace x with −x : ln 11. (a) 1−x 1+x 1 1 = −2 x + x3 + x5 + · · · 3 5 1 1 = = 1 + (1 − x) + (1 − x)2 + · · · + (1 − x)k + · · · x 1 − (1 − x) = 1 − (x − 1) + (x − 1)2 − · · · + (−1)k (x − 1)k + · · · (b) (0, 2) 12. (a) 1/x0 1 = = 1/x0 − (x − x0 )/x2 + (x − x0 )2 /x3 − · · · + (−1)k (x − x0 )k /xk+1 + · · · 0 0 0 x 1 + (x − x0 )/x0 (b) (0, 2x0 ) 13. (a) (1 + x + x2 /2 + x3 /3! + x4 /4! + · · ·)(x − x3 /3! + x5 /5! − · · ·) = x + x2 + x3 /3 − x5 /30 + · · · (b) (1 + x/2 − x2 /8 + x3 /16 − (5/128)x4 + · · ·)(x − x2 /2 + x3 /3 − x4 /4 + x5 /5 − · · ·) = x − x3 /24 + x4 /24 − (71/1920)x5 + · · · 1 1 16 x ··· 14. (a) (1 − x2 + x4 /2 − x6 /6 + · · ·) 1 − x2 + x4 − 2 24 720 (b) 4 1 + x2 + · · · 3 1 1 5 1 + x − x2 + x3 − · · · 3 9 81 3 25 331 6 x +··· = 1 − x2 + x4 − 2 24 720 11 1 41 = 1 + x + x2 + x3 + · · · 3 9 81 399 Chapter 11 15. (a) (b) 16. (a) (b) 1 =1 cos x sin x = ex 1− x− 12 1 1 x + x4 − x6 + · · · 2! 4! 6! x5 x3 + − ··· 3! 5! 1+x+ 1 5 61 6 x + ··· = 1 + x2 + x4 + 2 24 720 x2 x3 x4 + + + ··· 2! 3! 4! 1 1 = x − x2 + x3 − x5 + · · · 3 30 tan−1 x 2 2 = x − x3 /3 + x5 /5 − · · · / (1 + x) = x − x2 + x3 − x4 · · · 1+x 3 3 1 5 7 ln(1 + x) = x − x2 /2 + x3 /3 − x4 /4 + · · · / (1 ...
View Full Document

This document was uploaded on 02/23/2014 for the course MANAGMENT 2201 at University of Michigan.

Ask a homework question - tutors are online